THE DETERMINANTS OF THE INFLOW OF INDONESIAN MIGRANTS WORKERS INTO MALAYSIA - Sofia Ratna Sari Harahap; Saad Mohd Said; Fatimah Said (Universitas Trisakti, 2009)
This study utilizes the push and pull theory as described in the Lowry (1966) spatial interaction model to estimate the determinants of Indonesian migrant workers into Malaysia during 1997-2005. The dependent variable used in this study is the number of Indonesian migrant workers and the independent variables are the income per capita in Malaysia and the unemployment rates in Indonesia. The regression model is estimated by using the ordinary least squares (OLS) technique. The result shows that both income per capita and unemployment rates have positive effects on Indonesian migrant workers into Malaysia. Hence, the findings support the push and pull theory where increases in income per capita in Malaysia acts as a pull factor that attract Indonesian workers into Malaysia. Whereas high unemployment rates in Indonesia is a push factor which encourages Indonesian workers to migrate. However, as compared to high wage rate in Malaysia, the existence of unemployment in Indonesia is found to be the main reason for the migration Indonesian workers into Malaysia. Keywords: Indonesian migrant workers, income per capita, unemployment rates, Malaysia.